Students' Perceptions toward the Implementation of YouTube-Based Digital Storytelling to Improve EFL Speaking Skills: A Case Study of Eleventh Grade - Eva Widyaningrum; Ma’mum, Nadiah Ma’mum (Lembaga Teewan Journal Solutions, 2026)
This study examines the implementation of Digital Storytelling (DST) and students’ perceptions of its use in improving English as a Foreign Language (EFL) speaking skills among 11th-grade students at Walisongo High School in Semarang. A qualitative case study design was employed, involving 13 students as participants. Classroom observations were conducted on all 13 participants, while semi-structured interviews were conducted with four students selected based on their active and frequent involvement during DST activities. Data analysis followed the Miles and Huberman technique, which includes data reduction, data presentation, and drawing conclusions. Findings from classroom observations confirmed that DST was effectively implemented through the structured framework of “watching, analyzing, and retelling,” with all 14 observation indicators recorded positively. Interview findings revealed consistently positive student perceptions across five themes: learning engagement, speaking confidence, speaking fluency, pronunciation and vocabulary development, and challenges. In terms of speaking skills, DST activities improved students’ fluency by reducing hesitation through repeated watching and retelling exercises, enhanced pronunciation awareness through imitation of native English speakers in YouTube videos, and expanded the use of contextual vocabulary during oral retelling. The students also reported increased confidence in speaking and reduced anxiety before oral presentations, which was attributed to their familiarity with the story content gained through repeated viewings. However, students faced challenges in fluently and grammatically correctly restructuring the story’s content when retelling it directly, reflecting the gap between the receptive and productive stages commonly experienced by English as a Foreign Language (EFL) learners. In line with Krashen’s Affective Filter Hypothesis and constructivist learning principles, the framework of watching, analyzing, and retelling proved to be an accessible strategy that requires few resources to support the development of English as a foreign language speaking skills in high school settings in Indonesia.